Constitutional Mismatch Repair Deficiency in Israel: High Proportion of Founder Mutations in MMR Genes and Consanguinity. Issue 3 (6th November 2015) - Baris, Hagit N.; Barnes‐Kedar, Inbal; Toledano, Helen; Halpern, Marisa; Hershkovitz, Dov; Lossos, Alexander; Lerer, Israela; Peretz, Tamar; Kariv, Revital; Cohen, Shlomi; Half, Elizabeth E.; Magal, Nurit; et al.
Abstract : Background: Heterozygous germline mutations in any of the mismatch repair (MMR) genes, MLH1, MSH2, MSH6, and PMS2, cause Lynch syndrome (LS), an autosomal dominant cancer predisposition syndrome conferring a high risk of colorectal, endometrial, and other cancers in adulthood. Offspring of couples where both spouses have LS have a 1:4 risk of inheriting biallelic MMR gene mutations. These cause constitutional MMR deficiency (CMMRD) syndrome, a severe recessively inherited cancer syndrome with a broad tumor spectrum including mainly hematological malignancies, brain tumors, and colon cancer in childhood and adolescence. Many CMMRD children also present with café au lait spots and axillary freckling mimicking neurofibromatosis type 1. Procedure: We describe our experience in seven CMMRD families demonstrating the role and importance of founder mutations and consanguinity on its prevalence. Clinical presentations included brain tumors, colon cancer, lymphoma, and small bowel cancer. Results: In children from two nonconsanguineous Ashkenazi Jewish (AJ) families, the common Ashkenazi founder mutations were detected; these were homozygous in one family and compound heterozygous in the other. In four consanguineous families of various ancestries, different homozygous mutations were identified. In a nonconsanguineous Caucasus/AJ family, lack of PMS2 was demonstrated in tumor and normal tissues; however, mutations were not identified. Conclusions: CMMRD is rare, but, especially in areas where founder mutations for LS and consanguinity are common, pediatricians should be aware of it since they are the first to encounter these children. Early diagnosis will enable tailored cancer surveillance in the entire family and a discussion regarding prenatal genetic diagnosis.